ENVIRONMENTAL IMPACTS OF THE FOOD ESTATE POLICY IN GUNUNG MAS REGENCY, CENTRAL KALIMANTAN: A DPSIR ANALYSIS - Alpriyanto Situmorang (Jurnal Pemerintahan Dan Keamanan Publik (JP dan KP), 2026)
The implementation of Indonesia's Food Estate policy has generated growing concerns regarding its environmental sustainability despite its objective of strengthening national food security. This study analyzes the environmental consequences of the Food Estate program in Gunung Mas Regency, Central Kalimantan, using the Driving Forces–Pressures–State–Impacts–Responses (DPSIR) framework. A qualitative case study based on document analysis was conducted using policy documents, environmental reports, and previous studies. Results indicate that the policy’s focus on large-scale agricultural expansion has generated environmental pressures through forest-to-cassava field conversion. Based on the reviewed documents, these pressures are associated with reported soil erosion risks, declining soil quality, disruption of upstream hydrological functions, and carbon emissions related to land clearing. The reviewed evidence also indicates that land conversion activities have been associated with downstream flooding events, low cassava productivity, and increased vulnerability to forest fires. The DPSIR analysis also shows that these environmental problems are closely linked to the policy design, particularly the site selection and implementation strategies. Based on the findings, this study suggests policy responses including a comprehensive policy evaluation, better site selection, gradual land development, land rehabilitation and integrated disaster mitigation measures. By systematically mapping the causal relationships between policy interventions and environmental change, this study contributes to evidence-based policy evaluation for balancing national food security objectives with environmental sustainability and local community welfare.